The Role of Alumni In Curriculum Development In Early Childhood Islamic Education Program (PIAUD) UIN Sumatra Utara Medan - Muhammad Basri; Ahmad Syukri Sitorus (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the role of alumni in developing the curriculum for the PIAUD FITK study program, State Islamic University of North Sumatra, Medan. This research uses a qualitative approach with a descriptive analytical study method. Obtaining research data using observation techniques, interviews and documentation studies. Analysis of research data using reduction techniques, data presentation, and drawing conclusions. Furthermore, researchers tested the validity of the research data using data triangulation techniques. The results of this study concluded that the role of PIAUD alumni in the development of the PIAUD curriculum, it was found that 1) there were several courses that were needed that could boost the knowledge and skills of PIAUD alumni including practical science courses, computers and multimedia, as well as STEAM-based learning which became learning early childhood at this time, 2) the portion of learning in class with learning in the field is not yet appropriate. 3) the qualifications of the lecturers who teach the course are not in accordance, and 4) there needs to be an additional duration in the implementation of field experience practice (PPL).